A New Spontaneously Transformed Syngeneic Model of High-Grade Serous Ovarian Cancer with a Tumor-Initiating Cell Population - McCloskey, Curtis W.; Goldberg, Reuben L.; Carter, Lauren E.; Gamwell, Lisa F.; Al-Hujaily, Ensaf M.; Collins, Olga; Macdonald, Elizabeth A.; Garson, Kenneth; Daneshmand, Manijeh; Carmona, Euridice; Vanderhyden, Barbara C. (Frontiers in Oncology, 2014)
Improving screening and treatment options for patients with epithelial ovarian cancer has been a major challenge in cancer research. Development of novel diagnostic and therapeutic approaches, particularly for the most common subtype, high-grade serous ovarian cancer (HGSC), has been hampered by controversies over the origin of the disease and a lack of spontaneous HGSC models to resolve this controversy. Over long-term culture in our laboratory, an ovarian surface epithelial (OSE) cell line spontaneously transformed (STOSE). The objective of this study was to determine if the STOSE cell line is a good model of HGSC. STOSE cells grow faster than early passage parental M0505 cells with a doubling time of 13h and 48h, respectively. STOSE cells form colonies in soft agar, an activity for which M0505 cells have negligible capacity. Microarray analysis identified 1755 downregulated genes and 1203 upregulated genes in STOSE compared to M0505 cells, many associated with aberrant Wnt/β-Catenin and Nf-κB signaling. Upregulation of Ccnd1 and loss of Cdkn2a in STOSE tumors is consistent with changes identified in human ovarian cancers by The Cancer Genome Atlas. Intraperitoneal injection of STOSE cells into SCID and syngeneic FVB/N mice produced pan-CK+, WT1+, inhibin- and PAX8+ tumors, a histotype resembling human HGSC. Based on evidence that a SCA1+ stem cell-like population exists in M0505 cells, we examined a subpopulation of SCA1+ cells that is present in STOSE cells. Compared to SCA1- cells, SCA1+ STOSE cells have increased colony-forming capacity and form palpable tumors 8 days faster after intrabursal injection into FVB/N mice. This study has identified the STOSE cells as the first spontaneous murine model of HGSC and provides evidence for the OSE as a possible origin of HGSC. Furthermore, this model provides a novel opportunity to study how normal stem-like OSE cells may transform into tumor-initiating cells.